Penguatan siwa Madrasah Tsanawiyah Ihamul Hasan Racek Tiris terhadap Aspek-aspek Perkembangan - Agil Agil; Antoni Alan; Endah Tri Wisudaningsih (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service program aims to strengthen the developmental aspects of students at Madrasah Tsanawiyah Ihamul Hasan Rcek Tiris, covering physical, cognitive, social, and emotional development holistically. The program was implemented through a collaborative participatory model involving teachers, students, and a university mentoring team. The activities consisted of an initial assessment, training sessions, consultations, counseling, character building, and a qualitative evaluation conducted over three months. The results show significant improvements in students’ learning motivation, active learning styles, self-confidence, social interaction skills, emotional stability, and healthy lifestyle habits. This strengthening program contributed to shaping students who are more independent, well-charactered, and adaptive to contemporary educational challenges. These findings align with holistic development theories emphasizing the integration of physical, cognitive, social, and emotional aspects to support optimal student growth. Overall, the program produced positive impacts and offers a sustainable model for student development within the madrasah setting.